Respuesta :

Answer:

f(x) + g(x) = 6x^2 + 28x + 36

Step-by-step explanation:

Thirty eight

You begin to solve this by writing it like this [just as you have it].

f(x) = x^2 + 5                    Now put g(x) where you see x

f(g(x)) = [g(x)]^2 + 5          Now substitute the right side of g(x) wherever you see g(x)

f(x - 4) = [x - 4]^2 + 5        Expand the brackets

f(x- 4) = x^2 - 8x + 16 + 5

f(x - 4) = x^2 - 8x + 21

=======================

Thirty Nine

f(x) = (x + 4)^2

g(x) = 5(x + 2)^2

Expand f(x)

f(x) = x^2 + 8x + 16

Expand g(x)

  • g(x) = 5(x^2 + 4x + 4)                    Remove the brackets
  • g(x) = 5*x^2 + 5*4x + 5*4              Perform the multiplication
  • g(x) = 5x^2 + 20x + 20                  

f(x) + g(x) = x^2 + 8x + 16 + 5x^2 + 20x + 20

f(x) + g(x) = 6x^2 + 28x + 36